Praktik Standard Contract pada PT iGrow Resources Indonesia Fatwa DSN MUI terhadap Standard Contract - Latifah Nur Aini; M. Ilham Tanzilulloh; Moch. Khoirul Fajar Sidik (Jurnal Antologi Hukum, 2022)
The standard contract is in the Fatwa of DSN MUI Number 117/DSN-MUI//II/2018 concerning Information Technology-Based Financing Services Based on Sharia Principles. In practice, the standard contract of PT iGrow Resources Indonesia contradicts the fatwa on profit sharing, disclaiming responsibility in the event of a loss. The objectives of this study include: knowing that iGrow's profit sharing is fluctuating and knowing that iGrow's disclaimer is contrary to the fatwa of DSN MUI. This study uses qualitative research methods, with the object of field research. The analytical method used in this study is the deductive method. The results of this study are: 1) iGrow's profit sharing is contrary to DSN Fatwa No. 117, namely financing is not allowed to have an element of usury while iGrow. It sets the amount of profit with an absolute nominal, which can be equated with usury; 2) The form of iGrow's disclaimer is contrary to the Fatwa of the MUI DSN. The standard iGrow contract states that iGrow transfers its responsibility to the capital manager in the event of a loss. Kontrak baku dalam Fatwa DSN MUI Nomor 117/DSN-MUI//II/2018 tentang Layanan Pembiayaan Berbasis Teknologi Informasi Berdasarkan Prinsip Syariah. Dalam prakteknya kontrak baku PT iGrow Resources Indonesia bertentangan dengan fatwa pada pembagian keuntungan, pelepasan tanggung jawab jika terjadi kerugian. Tujuan penelitian ini antara lain: mengetahui pembagian keuntungan iGrow bersifat fluktuatif dan mengetahui bentuk pelepasan tanggung jawan iGrow bertentangan dengan fatwa DSN MUI. Penelitian ini menggunakan metode penelitian kualitatif, dengan objek penelitian lapangan. Metode analisis yang digunakan dalam penelitian kali ini adalah metode deduktif. Hasil dari penelitian ini adalah: 1) Pembagian keuntungan iGrow bertentangan dangan Fatwa DSN No 117 yaitu pembiayaan tidak diperbolehkan ada unsur riba sementara iGrow menetapkan jumlah keuntungan dengan nominal mutlak, ini dapat dipersamakan dengan riba; 2) Bentuk pelepasan tanggung jawab iGrow bertentangan dengan Fatwa DSN MUI. Dalam kontrak baku iGrow disebutkan bahwa iGrow mengalihkan tanggung jawabnya kepada pengelola modal apabila terjadi kerugian.